Novel bioactive peptides demonstrating anti-dengue virus activity isolated from the Asian medicinal plant Acacia Catechu - Aussara Panya (2018)
© 2018 John Wiley & Sons A/S The therapeutic activities of food-derived bioactive proteins and peptides are attracting increased attention within the research community. Medicinal plants used in traditional medicines are an excellent source of bioactive proteins and peptides, especially those traditionally prepared by water extraction for use as tea or food supplement. In this study, novel bioactive peptides were isolated from enzymatic digests of 33 Thai medicinal plants. The inhibitory activity of each against dengue virus (DENV) infection was investigated. Of 33 plants, peptides from Acacia catechu extract demonstrated the most pronounced anti-DENV activity. Half maximal inhibitory concentration of 0.18 μg/ml effectively inhibited DENV foci formation. Treatment with 1.25 μg/ml crude peptide extract could reduce virus production less than 100-fold with no observable cell toxicity. Peptide sequences were determined by high-performance liquid chromatography and liquid chromatography–tandem mass spectrometry. Two bioactive peptides isolated from Acacia catechu inhibited DENV foci formation >90% at the concentration of 50 μM; therefore, they are recommended for further investigation as antiviral peptides against DENV infection.